A broadband filter with two transmission zeros adopting a new design method. Issue 2 (23rd December 2019) - Liu, Xiandong; Zhang, Zhonghai; Sun, Lingling; Su, Guodong
Abstract: A new design method was proposed in this article to insert transmission zeros in the broadband filters. In this method, the coupling line was connected to a certain position on the resonator. And then the coupling strength was adjusted by the connecting position. The open end of the resonator was hung and then the cross‐coupling was introduced to realize transmission zeros. This coupling method could add an adjustable parameter to improve the freedom of design and convenient to insert the transmission zeros. To verify this method, a highly selective coupled‐line microstrip filter with two transmission zeros was designed, fabricated, and measured. The measured results were in good agreement with the simulated ones. The return and insertion losses of the broadband filter were better than 18 and 2 dB, respectively. The relative bandwidth of the filter (FBW) was more than 68%. The rectangular coefficient (30 dB:1 dB) was less than 1.21.